Venous Sinus Stenosis with Prominent Emissary Veins: A New Common Cranial MRI Finding of Mucopolysaccharidosis I - Huang, Shiwei; Gupta, Ashish; Orchard, Paul; Lund, Troy; Nascene, David (American Journal of Neuroradiology, 2023)
SUMMARY: Mucopolysaccharidosis I-Hurler (MPSIH) syndrome is the most severe form of a group of hereditary lysosomal diseases. This study aims to describe previously unreported common cranial findings of sigmoid sinus stenosis with prominent emissary veins in MPSIH. A retrospective review was conducted of 66 patients with MPSIH who were treated at our institution. A total of 12 cranial MR imaging studies from 12 different patients demonstrating the venous sinus anatomy were reviewed. All 12 patients exhibited various degrees of sigmoid or transverse sinus stenosis. Eleven had various forms of emissary veins. Of those 12 patients with imaging of the venous sinuses, 9 had a lumbar puncture within the same months as the acquisition of the venogram without any correlation between elevated opening pressure and the severity of the venous sinus stenosis. Stenotic cerebral venous sinuses with associated emissary veins, common in patients with MPSIH, may be abnormal findings due to posterior fossa horns from glycosaminoglycan depositions rather than signs of elevated intracracranial pressure or requirement of CSF diversion.GAGglycosaminoglycanHSCThematopoietic stem cell transplantMPSIHmucopolysaccharidosis I-HurlerOPopening pressureVPventriculoperitoneal